2013
DOI: 10.15809/irriga.2013v18n3p471
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento De Grãos De Milho Sob Diferentes Sistemas De Irrigação Por Aspersão

Abstract: Rendimento de grãos de milho sob diferentes sistemas de irrigação...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Bergamaschi et al (2006) observed, from a ten-year field experiment in the city of Eldorado do Sul, RS, that total irrigation provided an increase of nearly 70% in maize yield compared with non-irrigated crops. Moreover, Vieira et al (2013) also found a significant increase in irrigated crops compared with non-irrigated plants.…”
Section: Introductionmentioning
confidence: 87%
“…Bergamaschi et al (2006) observed, from a ten-year field experiment in the city of Eldorado do Sul, RS, that total irrigation provided an increase of nearly 70% in maize yield compared with non-irrigated crops. Moreover, Vieira et al (2013) also found a significant increase in irrigated crops compared with non-irrigated plants.…”
Section: Introductionmentioning
confidence: 87%
“…For plant height, the hybrid 2B810 had 23% higher plant population when compared to the hybrid with the lowest plant height (MG 580). Although the irrigation depths did not differ significantly for plant height, other studies indicate the importance of water management in this crop (Kappes et al, 2011;Agostinho, 2011;Vieira et al, 2013). Rosa et al (2015) studied the behavior of 50 maize hybrids in response to two fertilization levels and verified mean heights of 213.1, 215.6, and 226.0 cm for hybrids DBK290, 2B810, and AS1633, respectively, in the region of Lucas do Rio Verde, MT, Brazil (Table 3).…”
Section: Rh (%)mentioning
confidence: 61%